2019
DOI: 10.1159/000500207
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Time to Surgery and Its Effect on Prognosis in Head and Neck Cancer

Abstract: <b><i>Background:</i></b> Recently, time to treatment initiation has been observed to be increasing specifically for head and neck cancer. It is acknowledged that the pattern of increase is reflective of the use of sophisticated diagnostic and therapeutic techniques but was also determined to affect survival. <b><i>Objectives:</i></b> Our study sought to further investigate time to surgery (TTS) for surgically treated patients to see whether TTS would influence p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…An association between delay and decreased overall survival was demonstrated in laryngeal cancer, oral cavity cancer and in the combination of the four common sites, although there are also studies that did not find this relationship [18,24,32,50]. Particularly in OPC, the majority of the studies did not support this association.…”
Section: Effect Of Delaymentioning
confidence: 95%
See 2 more Smart Citations
“…An association between delay and decreased overall survival was demonstrated in laryngeal cancer, oral cavity cancer and in the combination of the four common sites, although there are also studies that did not find this relationship [18,24,32,50]. Particularly in OPC, the majority of the studies did not support this association.…”
Section: Effect Of Delaymentioning
confidence: 95%
“…Notably, this association was mostly seen in the group with the longest TTI, the shortest significant delay being 45 days and the longest 90 days (Table 3). On the other hand, three studies showed no association between waiting time and survival [18,24,50].…”
Section: Effect Of Delay E Overall Survivalmentioning
confidence: 97%
See 1 more Smart Citation
“…We similarly did not identify an association with time to treatment and stage change. This is in contrast to a study of all head and neck malignancies that identified an association between time to treatment and upstaging, 25 although the extent of the impact on outcomes is inconsistent across different studies 26–28 …”
Section: Discussionmentioning
confidence: 61%
“…Academic facility was reported as a risk factor for prolonged TTI, as were transition of care [7,22,23,27], and insurance by Medicaid (in USA studies) [7,18,22,27]. Increasing comorbidity index (Charlson) was associated with increased risk of delay [19,29], although three other studies found no significant association between comorbidity and delay [22,24,27].…”
Section: All Four Common Sitesmentioning
confidence: 99%